1988
DOI: 10.1088/0031-9155/33/6/005
|View full text |Cite
|
Sign up to set email alerts
|

A portable reflectometer for the rapid quantification of cutaneous haemoglobin and melanin

Abstract: A portable reflectance instrument for the rapid quantification of cutaneous haemoglobin and melanin is presented. Light emitting diodes (LEDS) are used to illuminate the skin and a silicon photodiode to detect the light diffusely reflected from the surface. Reflectance measurements are made at only three wavelengths and the problems of pigment quantification consequent upon this are discussed. In addition to quantification of haemoglobin and melanin, qualitative information on the redox state of the blood may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 9 publications
1
76
0
2
Order By: Relevance
“…After data acquisition, the data were converted to ASCII text and exported to Microsoft Excel 2000 (Microsoft Corporation, Redmond, Washington). IHB and IOX were calculated with a modified version of methods by Feather et al [31][32] and Hagisawa et al [28]. Equations for the calculation of IHB and IOX for this study were where A is the absorption value at the specified wavelength (nanometer) in the TRS.…”
Section: Ischial Cutaneous Hemoglobin and Oxygenationmentioning
confidence: 99%
“…After data acquisition, the data were converted to ASCII text and exported to Microsoft Excel 2000 (Microsoft Corporation, Redmond, Washington). IHB and IOX were calculated with a modified version of methods by Feather et al [31][32] and Hagisawa et al [28]. Equations for the calculation of IHB and IOX for this study were where A is the absorption value at the specified wavelength (nanometer) in the TRS.…”
Section: Ischial Cutaneous Hemoglobin and Oxygenationmentioning
confidence: 99%
“…We also investigated the correlation between oxidative DNA damage and digitalized skin pigmentation level by using a reflectance spectrophotometer in each subject (12)(13)(14). On the basis of our epidemiologic results, we experimentally examined the effect of ultraviolet B (UVB) light irradiation on urinary 8-OHdG levels in hairless mice (HL-mice).…”
Section: Introductionmentioning
confidence: 99%
“…The LBS probe consists of a fiber bundle for illumination and an avalanche photodiode module placed 22 mm from the fiber bundle for detection. Feather et al 9 reported a portable diffuse reflectometer that uses nine LEDs at three visible wavelengths to illuminate skin and a photodiode to collect diffusely reflected light, through a 7-mm aperture. The LBS has a sensing depth over 1 cm, but is difficult to multiplex into a spectral imaging device because of the size of the device.…”
mentioning
confidence: 99%